«Rural Sectarianism» and «Urban Sectarianism» in the Soviet Propaganda of 1920-1930s (Based on the Materials of the Journal «Антирелигиозник») - Кучеренко, Маргарита (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article is devoted to the image of the social processes in sectarianism among the Soviet propagandists of the 1920-1930s (based on the materials of the journal «Антирелигиозник»). It is analyzed how imperial experience influenced the Soviet propagandists contemplation of the social characteristics of sectarianism. It was discovered that in the beginning of the period under review, sectarianism is described, mainly as a rural mass.Gradually the accents are changed, and Soviet propaganda begins to pay more attention to the spread of sects in cities. The causes of such transformation are revealed.